Association between change in employment status and new-onset depressive symptoms in South Korea – a gender analysis - Kim, Seung-Sup; Subramanian, S. V.; Sorensen, Glorian; Perry, Melissa J.; Christiani, David C. (Scandinavian Journal of Work, Environment & Health, 2012)
' ' OBJECTIVES ': 'This study aimed to investigate the association of change in employment status with new-onset depressive symptoms, particularly differences stemming from workers’ gender, in South Korea. ' ' METHODS ': 'We analyzed data from the ongoing Korean Welfare Panel Study. After excluding participants who had depressive symptoms at baseline (2007), we analyzed 2891 participants who became a precarious or permanent worker or unemployed at follow-up (2008) among waged workers who were permanent or precarious workers at baseline. Workers were classified as permanent workers if they had full-time, secure jobs and were directly hired by their employers; workers not meeting all these criteria were classified as precarious workers. Depressive symptoms were assessed annually using the 11-item Center for Epidemiologic Studies Depression Scale. To reduce potential bias due to pre-existing health conditions, we also examined the association in a subpopulation excluding participants with any pre-existing chronic disease or disability. ' ' RESULTS ': 'Compared to those who maintained permanent employment, workers who became unemployed following precarious employment had higher odds of developing depressive symptoms [odds ratio (OR) 2.30, 95% confidence interval (95% CI) 1.01–5.25]. In gender-stratified analyses, new-onset depressive symptoms were strongly associated with the change from precarious to permanent employment (OR 2.57, 95% CI 1.20–5.52) as well as the change from permanent to precarious employment (OR 2.88, 95% CI 1.24–6.66) among females; no significant association was observed in the male subpopulation. ' ' CONCLUSIONS ': 'This study found that changes from precarious to permanent work or from permanent to precarious work were associated with new-onset depressive symptoms among South Korean women.
Keywords: depression; depressive symptom; employment status; gender; gender difference; mental health; South Korea